Quality of care and satisfaction of patients treated at a dental chain. Lima–Peru, 2019–2020 - Fabian-Sánchez, Andrea Carolina (2022)
Objective: To evaluate the relationship between quality of care and degree of satisfaction of patients treated at a dental chain in Lima, Peru, from 2019 to 2020. Materials and methods: A quantitative, descriptive and cross-sectional study. Two surveys were administered: the SERVPERF model (consisting of five dimensions) and the satisfaction survey created by Ramírez (consisting of three dimensions). Both surveys were administered to patients treated during the 2019–2020 period. Results: Out of the 150 respondents, 93.30 % perceived a high quality of care (Partially agree and Totally agree) and 3.30 % disagreed with the quality of care (Totally disagree and Partially disagree). Therefore, the latter were included in the low-quality-of-care group. It was also found that 96.70 % (145) of the surveyed patients were satisfied with their care in the dental chain, 3.30 % (5) were dissatisfied, and none was moderately satisfied. Conclusions: It is concluded that there is a direct and statistically significant relationship between quality of care and patient satisfaction. In the reliability, sensitivity, security, empathy and tangible elements dimensions, patients’ perception of quality was high. Likewise, in the human, technical-scientific and environment dimensions, patients stated that they were satisfied with the care received.